ANALISIS SEGMENTASI TERHADAP KEPUTUSAN PEMBELIAN PRODUK EIGER DI BANDAR LAMPUNG - Ahmadi, Nanang Khoirul; -, Herlina (Jurnal Manajemen Magister Darmajaya, 2017)
Purchase decision is strongly affected by consumer behavior so that the purchase decision is needed for selling products. Moreover, the purchase decision is also the consumer behavior in effort to fulfill desire and need. In addition, the purchase decision is the process of deciding the attitude to purchase goods and services so that the consumer behavior needs its process because human experience changes in every moment. Changes directly affect the consumer behavior patterns including geographic, demographic, psychographic, and behavioral factors. The objective of this research was to determine whether the demographic and psychographic segmentation significantly affects the purchase decision on Eiger products in Bandar Lampung. Sample of this research was Eiger product users (550 people) in Bandar Lampung. The type of this research was a quantitative research with CHAID Exhaustive method. The result of this research was that there was an effect between the demographic segmentation and the purchase decision and there was an effect between psychographic segmentation and the purchase decision.Keywords: Segmentation, Purchase Decision